FREQUENCY OF ELECTROLYTE ABNORMALITIES IN PATIENTS WITH DECOMPENSATED CHRONIC LIVER DISEASE - ULLAH , M; MAAZ , .; RASHID , MF; ALI , I; NIAZ , M; KAMRAN , M (Biological and Clinical Sciences Research Journal, 2024)
Electrolyte abnormalities, particularly those involving sodium, potassium, magnesium, calcium, and phosphate, are commonly observed in patients with decompensated chronic liver disease (DCLD). Objective: The basic aim of the study is to find the frequency of electrolyte abnormalities in patients with decompensated chronic liver disease. Methodology: This cross-sectional observational study was carried out at Lady Reading Hospital, Peshawar, from January 2024 to May 2024. The study included a total of 235 patients diagnosed with decompensated chronic liver disease. Patients aged >18 years with a confirmed diagnosis of chronic liver disease in the decompensated stage, characterized by complications such as ascites, variceal bleeding, or hepatic encephalopathy. Results: Data were collected from 235 patients with a mean age of 52.3 ± 10.4 years, with a male predominance (59.6%). Common comorbidities among participants included hypertension (45.5%), diabetes mellitus (30.6%), and chronic hepatitis C infection (60.9%). These underlying conditions highlight the complex health profile of patients with decompensated chronic liver disease, which may further influence electrolyte imbalances and overall disease outcomes. Sodium levels deviated from the normal range in 67.2% of patients, with hyponatremia observed in 60.9% (mean sodium level 132.5 ± 6.3 mmol/L) and hypernatremia in 6.4%. Potassium abnormalities were found in 49.4% of patients, with 37.0% exhibiting hypokalemia and 12.3% showing hyperkalemia (mean potassium level 4.0 ± 0.7 mmol/L). Hypocalcemia was prevalent in 44.3% of patients, with an average calcium level of 8.0 ± 0.6 mg/dL. Hypomagnesemia and hypophosphatemia were less common but still present in 25.1% and 20.4% of patients, respectively. These abnormalities underscore the need for vigilant electrolyte monitoring in DCLD patients. Conclusion: It is concluded that electrolyte abnormalities are highly prevalent in patients with decompensated chronic liver disease and are strongly associated with increased disease severity, complications, and poor outcomes.